Extraction of resveratrol with the enzyme preparation Pectinol F-RKM 0719 produced by the strain Aspergillus awamori F-RKM 0719 (Experimental biology, 2019)
Resveratrol is natural phytoalexin with pronounced therapeutic and prophylactic properties, it is part of the grape skin composition. However, due to the fact that it  is in a bound state, the use of it by organism significantly reduced. Therefore,  for the extraction of  resveratrol is a need to use the enzyme preparations. The purpose of this study is maximize the recovery of resveratrol from the grape skin.During ripening of grape, the mass concentration of resveratrol increases, and the maximum value is reached in the Caberno Sauvignan variety - 467 mg / dm3. In all experiments on the extraction of resveratrol from grape squeeze by the strain Aspergillus awamori F-RKM 0719 and the enzyme preparation Pectinol F-RKM 0719 an increase in the quantity of resveratrol is observed. In experiments with Caberno Sauvignan, the amount of resveratrol was maximal and increased from 392.66 control sample, when using the strain Aspergillus awamori F-RKM 0719 - 497.66, and when resveratrol was extracted by the enzyme preparation Pectinol F-RKM 0719  - 699.62 mg / dm3 .Studies have shown the possibility of using the Caberno Sauvienne grape variety and the enzyme preparation Pectinol F-RKM 0719, which significantly increases the amount of  extracted resveratrol.Keywords: resveratrol, enzyme preparation Pectinol F-RKM 0719, strain Aspergillus awamori F-RKM 0719, fermented juice.